Factors influencing manure application by farmers in semi-arid West Africa - Williams, Timothy O. (Springer, 1999)
Animal manure is one of the principal sources of nutrients for soil fertility maintenance and crop production in semi-arid west Africa. Farm-level decisions concerning the use of manure are governed by socioeconomic and institutional factors, as much as they are by agronomic ecological concerns. This paper analyses the cultural and socio-economic factors affecting manure use decisions in parts of semi-arid West Africa using a logit model. The results show that the major factors that positively influence farmers' manuring decisions are the farmer's own herd size, contractual arrangements between herders and farmers for manure, seasonal-migration and its effect on livestock investment and the proportion of cultivated land owned by the farmer. Factors found to negatively affect manure use are farm size, distance of fields to the homestead, the proportion of cultivated land recently under fallow and land-labour ratio. The paper concludes by suggesting strategies for removing the constraints to efficient manure utilisation and soil fertility improvement in semi-arid West Africa.